Prophetic Leadership Paradigm and Madrasah Teacher Performance: A Comparative Study in Banten - Ahmad Rifaudin; Wasehudin Wasehudin; Makmur Harun (International Journal of Nusantara Islam, 2026)
This study analyzes the application of the prophetic leadership paradigm in madrasah educational institutions and its influence on teacher performance in Banten Province. Using a comparative qualitative method, the study was conducted in four leading madrasahs: MAN Insan Cendekia Serpong, MAN 2 Serang City, MAN 2 Pandeglang, and MAS Miftahul Huda Pasirnangka Tigaraksa. Data were collected through in-depth interviews, participatory observation, and documentation studies, then analyzed using the Miles and Huberman model. The results of the study indicate that prophetic leadership based on prophetic values (shiddiq, amanah, tabligh, and fathanah) is proven to be a key factor in improving the performance of madrasah teachers. The three dimensions of prophetic leadership—spiritual transcendence, humanity, and prophetic morals—are implemented with different patterns in each madrasah according to institutional characteristics. MAN IC Serpong stands out in professionalism and modern management systems; MAN 2 Serang City in participatory communication and moral-bureaucratic balance; MAN 2 Pandeglang in spirituality and religious culture. Meanwhile, MAS Miftahul Huda excels in sincerity and personal exemplary behavior. The principal's exemplary behavior is a dominant factor in fostering trust, loyalty, and intrinsic motivation among teachers, thereby improving lesson planning, innovative teaching methods, work discipline, and socio-religious involvement. This study recommends internalizing prophetic values in the madrasah management system and integrating them into the Islamic educational leadership training curriculum.